Enhanced Light Trapping and Power Conversion Efficiency in Ultrathin Plasmonic Organic Solar Cells: A Coupled Optical-Electrical Multiphysics Study on the Effect of Nanoparticle Geometry - In, Sungjun; Mason, Daniel R.; Lee, Hyunho; Jung, Mi; Lee, Changhee; Park, Namkyoo (AMER CHEMICAL SOC, 2015)
Plasmonic effects associated with localized surface plasmon (LSP) resonances such as strong light trapping, large scattering cross-section, and giant electric field enhancement have received much attention for the more efficient harvesting of solar energy. Notably, even as the thickness of the active layer is significantly reduced, the optical absorption capability of a solar cell could be maintained with the incorporation of plasmonic effects. This is especially important for the development of bulk heterojunction (BHJ) organic solar cells (OSCs), where the short exciton diffusion length, low carrier mobility, and strong charge recombination in organic materials strongly favors the use of optically thin active layers (<100 nm). However, the disappointing performance improvements obtained with plasmonic effects in the majority of BHJ OSCs realized to date suggests that plasmonic effects are yet to be fully taken advantage of; for example, in thick active layer OSCs (>100 nm), the optical absorption is already high, even in the absence of plasmonic effects, while in thin active layer OSCs (<100 nm), insufficient attention has been given to the analysis of plasmonic effects, such as the impact of plasmonic nanoparticle (NP) geometrical factors on the directional scattering efficiency. In this paper, we propose and demonstrate that the geometrical tuning of spheroidal plasmonic nanoparticles (NPs) could enable the full exploitation of plasmonic effects, providing dramatic improvements to the light absorption and energy harvesting capability of ultrathin film BHJ OSCs. Our theoretical analysis demonstrates a dramatic enhancement in optical absorption of similar to 60% with spheroidal NPs embedded in a BHJ OSC device with ultrathin, <100 nm active layer, as compared to an NP absent reference device. These improvements are explained according to enhanced scattering of light into the active layer plane, spectral broadening of absorption resonances, in addition to an increased plasmonic modal volume, exhibited near LSP resonances of spheroidal NPs with optimal eccentricity. The result of our coupled optical-electrical device simulations also proves that the outstanding optical absorption enhancement obtained from the proposed device indeed translates into significant electrical performance gains; such as a similar to 30% increase in the short-circuit current and similar to 20% improvement in the power conversion efficiency (PCE).